A inviolabilidade do domicílio e seus limites: o caso do flagrante delito (The inviolability of the home and its limits: the case of flagrante delict) - Sarlet, Ingo Wolfgang (2013)
o presente artigo analisa o direito fundamental à inviolabilidade de domicílio em face dos seus limites, no caso, o da prisão em flagrante delito e das circunstâncias que justificam, nos casos de crime permanente, a sua legitimação em face da ordem jurídica, pena de configuração da ilicitude da prova obtida.this article analyzes the fundamental right to home inviolability in the light of its admitted restrictions, namely the case of inprisonment during the commission of a crime (in flagrante delicto) and the circunstances in which this is allowed in the case of continuous crime in order not to configurate inadmissible evidence.